The Relationship of Nurses Response Time With Family Anxiety of Ed Patients Based on Triage at RSU Muslimat Ponorogo - Rahmania Ambarika; Putri Mayasari; Novita Ana Anggraini (Journal of Global Research in Public Health, 2024)
The patient's response time is required ≤ 5 minutes to get help appropriate to the emergency to increase safety. Opportunities can be increased with prompt handling. The tendency for patients treated in the ER to expect quick treatment. Perceptions of delays in treatment can cause patient anxiety. The aim of this research is to analyze the relationship between nurse response time and emergency room patient family anxiety based on triage at RSU Muslimat Ponorogo. This research design is cross sectional with a sample size of 123 respondents. The sampling technique uses purposive sampling. Research questionnaires use questionnaires to test clinical profile correlations. Slow response time will be perceived by the patient's family as having no acceptance or rejection of him and is a factor in increasing anxiety. This will cause an increase in sympathetic nerves which will cause symptoms such as dizziness, shaking, headaches, sweating, and increased pulse rate. From this research data, it shows that the nurse's response time is slow, and the patient's family experiences severe anxiety. Based on the results of the Spearment correlation test, P value = 0.024 (<0.05), which means that H0 is rejected and H1 is accepted, which means there is a relationship between nurse response time and patient family anxiety in the emergency room at RSU Muslimat Ponorogo. In each triage, there are differences in the level of anxiety felt by the patient's family. in the green triage most experienced mild anxiety, in the yellow triage most experienced moderate anxiety, in the red triage most experienced severe anxiety and in the black triage the majority experienced very severe anxiety.